Комплекс петроглифов с христианской символикой в гроте близ Баклы - Оксиненко, П.В.; Белый, А.В. (Материалы по археологии, истории и этнографии Таврии, 2005)
Известный археологический памятник Юго-Западного Крыма - Баклинское городище - замыкает на северо-востоке цепь “пещерных городов”, протянувшуюся от Севастополя до междуречья Бодрак-Альма в пограничной со степью полосе предгорья. Область сосредоточения объединенных этим названием средневековых
укреплений, открытых поселений и скальных монастырей находилась в сфере влияния византийского Херсона - главного форпоста империи в Северном Причерноморье. Усиление в Таврике позиций Византии сопровождалось распространением христианского вероучения и развернувшимся на землях варваров церковным строительством. In the neighbourhood of the early-medieval fortified settlement of Bakla several Christian churches and necropolises of different periods have been discovered. It enables us to speak about the formation of a rather large religious center here. In 2000 in the rock precipice, not far from the fortified settlement a new unusual Christian monument in grottos “Vostochny” (Eastern) and “Zapadny” (Western) was found; the number and diversity of crosses (more than 300) impress. There were complex framework structures, shelves and niches synchronous to petroglyphs. Judging by the complexity of wooden constructions and accumulation of religious symbols, rock complex, despite its out-of- the-way position was meant for massive attendance. Unusual concentration of the pictures of crosses verifies the fact that this place was a Christian sacred object of worship of special honour. The emergence of such a rock cult complex is dated back to the period of Christianization (Baptizing) of Taurica extended from the 6th - up to the 8th -9th centuries.